Distracting people from sources of discomfort in a simulated aircraft environment - Lewis, Laura; Harshada, Patel; Cobb, Sue; D'Cruz, Mirabelle; Bues, Matthias; Stefani, Oliver; Tredeaux, Grobler (IOS Press, 2016)
BACKGROUND: Comfort is an important factor in the acceptance of transport systems. In 2010 and 2011, the European Commission (EC) put forward its vision for air travel in the year 2050 which envisaged the use of in-flight virtual reality. This paper addressed the EC vision by investigating the effect of virtual environments on comfort. Research has shown that virtual environments can provide entertaining experiences and can be effective distracters from painful experiences. OBJECTIVE: To determine the extent to which a virtual environment could distract people from sources of discomfort. METHODS: Experiments which involved inducing discomfort commonly experienced in-flight (e.g. limited space, noise) in order to determine the extent to which viewing a virtual environment could distract people from discomfort. RESULTS: Virtual environments can fully or partially distract people from sources of discomfort, becoming more effective when they are interesting. They are also more effective at distracting people from discomfort caused by restricted space than noise disturbances. CONCLUSIONS: Virtual environments have the potential to enhance passenger comfort by providing positive distractions from sources of discomfort. Further research is required to understand more fully the reasons why the effect was stronger for one source of discomfort than the other.